Improving Primary Healthcare: Applying Grapevine (Vitis vinifera) Principles to Lebanon’s Vision 2030 - Karim W. Barake; Aaron Kinyu Hoshide; Salim M. Adib; Kimberly Samaha (Healthcare, 2026)
Background/Objectives: While Lebanon’s Vision 2030 prioritizes strengthening Lebanon’s chronically constrained, fragmented, and shocked primary healthcare system, implementation is hindered by weak sensing mechanisms, misaligned spatial distribution, and poorly integrated referral pathways. This study develops a preliminary, context-specific, systems-level healthcare policy assessment and framework for primary healthcare reform by applying biomimicry principles derived from the drought-resistant root architecture of grapevine (Vitis vinifera). Methods: Publicly available data from the Lebanese Ministry of Public Health, national assessments, and non-governmental organization registries were synthesized to examine mismatches between healthcare need and service capacity. We developed a preliminary healthcare Need Score for Lebanon’s eight governorates based on clinical demand, capacity strain, and socioeconomic vulnerability. An Agent-Based Approach within a biomimicry framework was used to translate grapevines’ biological strategies into healthcare policy design principles. Results: Structural deficiencies were identified in Lebanon’s primary healthcare system, including absence of standardized need-based sensing, uneven geographic service distribution, weak-referral integration, and limited adaptive feedback. Our preliminary Need Score was used four clinical demand indicators for iron deficiency, neonatal and maternal deaths, pre-mature births and birth defects, and disease incidence. Service-capacity strain indicators were primary healthcare center density and staffing. Finally, socioeconomic vulnerability indicators were percentages for non-Lebanese population and food insecurity. The proposed policy framework can translate frontline stress signals to rule-based responses, guide adaptive redistribution of capacity, and structurally anchor primary healthcare centers to referral hubs through defined catchments and electronic referral loops. Conclusions: Biomimicry can shed insight into how to improve primary healthcare governance under chronic scarcity. Need Scores and biological resilience principles can strengthen primary healthcare systems in low-resource settings while aligning with healthcare policy objectives like those in Lebanon’s Vision 2030.